Using factor analysis to assess the key factors influencing the success completion of a public school project in Malaysia - Mohd Nasir, Siti Rashidah; Abd.Majid, Muhd Zaimi (2008)

(untitled)
The study of project success is considered to be a means to improve the effectiveness of project. Generally, successful project can be defined as the overall achievement of project goals and expectations. This goal and expectation relate to a variety of elements including technical, financial, educational, social and professional issues. This study reports a factor analysis of seventeen (17) major factors influencing the successful completion of construction project that were determined in an assessment of 141 respondent. The respondent are from the Public Work Department (PWD), Education Work Branch (EWB) of PWD and the Contractors who has completed the public school project for PWD. A principal axes method of factor analysis with orthogonal rotation revealed five (5) significant factors representing underlying structure for the success of project completion. Factor 1 accounts for 16.591% of variance compared to Factor 2 accounts for 16.386% of variance, Factor 3 accounts for 13.711%, Factor 4 accounts for 13.657% and Factor 5 accounts for 13.098% of variance. Oblique rotation was also carried out and interrelationships between the factors were determined and discussed.